Kedudukan dan Besaran Mahar dalam Pernikahan Menurut Pendapat Para Ulama’ - M Burhanudin (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
In the Fiqh of Marriage, Mahar/shodaq is a gift from the prospective husband to his prospective wife as an expression of love, not as wages or compensation for the woman, the amount of dowry which can vary from one person to another. Then, in relation to the marriage the Kabul consent, So the question arises what is the urgency of the dowry (shodaq) and its position in marriage? Is the mention of the dowry required in the Kabul consent? What is the actual dowry? To answer the problems above, this article was written,, aims to examine and analyze the views of dowry, both from a legal perspective its position and amount in marriage and what are the consequences of a marriage that does not mention a dowry, also includes arguments and as well as discuss them using descriptive methods of analysis.The results of this analysis show that the law of dowry in marriage is obligatory but is not included in the pillars and conditions of marriage. There is no specific maximum limit according to the majority of scholars madzhab, As for the minimum nominal, there are 2 opinions, the first is the Shafi'iyah madzhab: there is no minimum limit, and the Malikiyah and Hanafiyah madzhab require a minimum dowry of 10 Dirhams, This is the amount of the nishab for cutting off a hand in the event of theft. And the dowry is recommended to be mentioned in the Kabul consent Iqtida'an with the Prophet Muhammad SAW.